2019
DOI: 10.3892/ijo.2019.4933
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer cell‑secreted exosomal miR‑21 activates the PI3K/AKT pathway in macrophages to promote cancer progression

Abstract: Tumour-associated macrophages (TAMs) compose a major component of the tumour microenvironment and form in this microenvironment prior to cancer metastasis. However, the detailed mechanisms of TAM remodelling in the context of bladder cancer have not been clearly defined. The present study collected exosomes from the conditioned medium of human bladder T24 cancer cells. The effects of macrophages treated with exosomes derived from T24 cells on bladder cancer cell migration and invasion were analysed by Transwel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 52 publications
1
67
0
1
Order By: Relevance
“…Recently, it was reported that colon cancer-derived exosomes carrying miR-1246 induced macrophages toward a TAM phenotype [51]. Similarly, other studies have shown that cancer-derived exosomes can carry miRNAs that promote the macrophage transition to TAMs in several types of cancers, including ovarian [52,53], bladder [54], head and neck [55], skin, and lung cancer [56]. The PI3K/AKT signaling pathway is directly associated with macrophage polarization, thereby promoting cancer migration, invasion, and drug resistance [57].…”
Section: Tumor-associated Macrophage Exosomal Mirnas Enhance Drug Resmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, it was reported that colon cancer-derived exosomes carrying miR-1246 induced macrophages toward a TAM phenotype [51]. Similarly, other studies have shown that cancer-derived exosomes can carry miRNAs that promote the macrophage transition to TAMs in several types of cancers, including ovarian [52,53], bladder [54], head and neck [55], skin, and lung cancer [56]. The PI3K/AKT signaling pathway is directly associated with macrophage polarization, thereby promoting cancer migration, invasion, and drug resistance [57].…”
Section: Tumor-associated Macrophage Exosomal Mirnas Enhance Drug Resmentioning
confidence: 95%
“…The PI3K/AKT signaling pathway is directly associated with macrophage polarization, thereby promoting cancer migration, invasion, and drug resistance [57]. Several studies have reported that exosomes released by cancer cells modulate PI3K/AKT pathway-related genes in macrophages to promote TAM polarization [54,[58][59][60].…”
Section: Tumor-associated Macrophage Exosomal Mirnas Enhance Drug Resmentioning
confidence: 99%
“…Independently of the mechanism, EVs seem to induce a TAM-like phenotype in peritumoral macrophages [ 6 , 25 ]. To this respect, recent observations reported miRNA molecules as active participants in this process [ 26 ]. For example, Valadi and collaborators demonstrated the exosome-mediated transfer of different types of RNA, including miRNAs, between cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these results demonstrate that PC3-derived EVs contain important signaling molecules, such as miRNA Let-7b, involved in the generation of a tumor-promoting microenvironment and suggest their potential use as targets for cancer therapy [ 26 ]. Moreover, the urgent need for new biomarkers for diagnosis and risk-stratification in prostate cancer [ 30 , 31 , 32 ] might lead to the use of EV-loaded miRNA Let-7b as a candidate biomarker for tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…EMT was induced by exosomal miR-663b in bladder cancer [ 81 ]; lncRNA SOX2 overlapping transcript (Sox2ot) in pancreatic ductal adenocarcinoma (PDAC cells) [ 82 ]; and TGF-β-enriched TEXs in myofibroblasts [ 83 ]. Migration of tumor cells was facilitated by the exosome-mediated transfer of αvβ6 in prostate cancer [ 84 ]; miR-21 in bladder cancer [ 85 ]; TAM derived exosomes in gastric cancer (GC) cells [ 86 ]; and lncRNA ubiquitin-fold modifier conjugating enzyme 1 (UFC1) in non-small cell lung carcinoma (NSCLC) [ 87 ]. Exosomal lncRNA zinc finger antisense 1 (ZFAS1) induced EMT and migration in GC cells [ 88 ].…”
Section: Texmentioning
confidence: 99%